Evaluation of the reality of applying a number of Iraqi institutional accreditation standards/study in a number of Iraqi public and private universities - Ali, Sally T.; AL_Basri, Abdulridha S. (Journal of Economics and Administrative Sciences, 2021)
The study aims to find out the extent to which several Iraqi institutional accreditation standards (governance and administration, scientific research, curricula) are applied in two public universities (Baghdad and Middle Technical University) and two private universities (Uruk and Al-Mansour College) by diagnosing strengths and weaknesses and proposing a mechanism and procedures to help educational institution aims to reduce or eliminate the gap. The study stems from the extent of application of several Iraqi institutional accreditation standards represented as it was worked on through observation and field coexistence to reach scientific and practical facts. The method of case study and comparison between public and private universities was adopted by using the checklist as a tool to collect data and information to help in a comprehensive and realistic analysis.  The study reached a set of results, the most prominent of which is the weak interest of the universities in the study sample in implementing the Iraqi institutional accreditation standards, which showed a gap between the actual performance of the universities and the indicators of the standards. This indicates that there are no specialized audit teams in the field of auditing quality management systems in higher education qualified according to the international standard (ISO 19001) to know the extent of conformity, as well as the absence of targeted plans to implement the indicators of those standards. Despite the existence of a Quality Assurance and Accreditation Council at the university that oversees the application of quality management systems in all university formations, it needs to intensify efforts to reach reliability in providing its services